Measurement of day and night neutrino energy spectra at SNO and constraints on neutrino mixing parameters - Ahmad, Q; Allen, R; Andersen, T; Anglin, J; Barton, J; Beier, E; Bercovitch, M; Bigu, J; Biller, S; Black, R; Blevis, I; Boardman, R; et al. (2002)
The measurement of day and night neutrino energy spectra at Sudbury Neutrino Observatory (SNO) and constraints on neutrino mixing parameters were presented. A global solar neutrino analysis in terms of matter-enhanced oscillations of two active flavors strongly favored the large mixing angle solution. Results obtained were the first direct measurements of the day-night asymmetries in the νe flux and the total ν flux from the Sun was deduced.